DIFFERENCES OF PREMENSTRUAL SYNDROME PREVENTIONS BEFORE AND AFTER THE FOOD CONSUMPTION WHICH CONTAINS ISOFLAVON IN ADOLESCENT - Ni Wayan Putri Utami; Ida Sofiyanti; Galeh Septiar Pontang (Universitas Andalas, 2018)
In adolescence, there will be some complaints, such as complaint of premenstrual syndrome (PMS). It defined as a physical, psychological or emotional symptom that appeared 7-10 days before menstruation. One of the treatments to reduce premenstrual syndrome is to eat food that contains isoflavones (68mg / day) because it has anti-estrogenic effect which is able to balance progesterone and etherogen hormones, which can decrease the complaints of premenstrual syndrome. This study aimed to determine the premenstrual syndrome complaints before and after the consumption of isoflavone food in tenth grade adolescents in Senior High School 2 Ungaran. This study was using pre-experimental design with one group pretest-posttest study design using simple random sampling totaling 16 respondents. Measurement of complaint of premenstrual syndrome used Premenstrual Shorted Assassement Form 1-6. Data analysis was performed using bivariate analysis using Paired-T test. Results of this study shown that 16 respondents who had complaints of premenstrual syndrome before the consumption of isoflavones food that contained isoflavones 14 respondents had moderate complaints and 2 respondents had light complaints. After the consumption of isoflavone food it showed that 9 respondents had moderate complaint and 7 respondents had light complaint. Based on statistical test, it was found that the mean value decreased from 26.18 to 21.12, the median from 15.00 to 21.50, SD ± 5.706 to ± 3.51 with p value of 0.011, which means p value <0.05. Conclusion of this study that there are differences in the complaint of premenstrual syndrome before and after the consumption of isoflavone food in tenth grade adolescents in Senior High School 2 Ungaran. Keywords: Isoflavone, premenstrual syndrome